Śrīkākuḷa girijana raitāṅga sāyudha pōrāṭa gātha : burrakatha - Venkateswara Rao, Kanuri, 1919- (Arunōdayasāṁskrtikasaṁstha, Āndhrapradēś ; pratulaku, Vimōcana, 1980)
Ballad on peasant uprising in Srikakulam District, Andhra Pradesh.